URBAN CLIMATE RESILIENCE AS AN APPROACH TO DESIGN FLOOD ADAPTIVE HOUSE (Case Study: Kampung Cieunteung RW 20, Baleendah, Kabupaten Bandung, Indonesia) - Negri, Patriot
Floods have become routine events that happened in Indonesia every rainy season. Data from the BNPB of the year 1815 - 2015, catastrophic floods are the most common disaster in Indonesia, which is about 31.7% of the total incidence of natural disasters in Indonesia. From these data, indicate that flood disaster is a priority to face with sustainable planning of flood resilience that makes the area affected by the flood to adapt. Flooding, generally occurs in the lowlands in the downstream river basin, which is generally become settlements with a high population density. Kampung Cieunteung RW 20 is an example of flooding in river basin that occurs in the downstream Citarum Hulu. This location used as a case study for this paper. Flooding is no longer seen in the perspective to resist, but as windows of opportunity to make that area become flood resilience. The solution is to approach flood resilience by adapting to the disaster if it occurs to site. This thesis focuses to meet the wishes of the people that don’t want to be relocated as well as providing an alternative to the government so that the people in Kampung Cieunteung settlement can be designed to adaptively against floods and flood settlements also can respond adaptively. Urban Climate Resilience as an approach to design flood adaptive house had been choosen by that reason. Urban Climate Resilience theory is focused on system categories that divided into safe failure, flexibility, modularity, diversity, and redundancy. Kampung Cieunteung administratively consists in Kelurahan Baleendah and divided into 4 RT (RT 01, 02, 03, and 04) and RW 20. The land area of Kampung Cieunteung RW 20 is 106,501.5 m2 or 10.65 hectares. Stages and research methodology made with sources of literature and field study. The study of literature sourced from secondary data from theoretical studies in Urban Climate Resilience, adaptive occupancy studies of flooding, precedent studies and studies Analytical Hierarchy Process (AHP) to know the opinion of the state and society to the main issues that need to be solved in the study area. Field studies derived from primary data processing in the form of surveys, observation, interviews with the government, and interviews with the questionnaires to the communities in Kampung Cieunteung. The concept of designing flood adaptive house is “Adaptive Cieunteung - Living with "Cai"” to make settlements easier to adapt or adjust to the situation in which they would remain adaptable if there has floods in Kampung Cieunteung. The concept of safe failure aims to adapt the floods in Kampung Cieunteung by making flood adaptive house that can live in two conditions, when it is not flooded on the land and when it is flooded on the water. Safe failure design concept by using ARCGIS to map the flow direction of water which will make the lake to be a place to hold water when there is flood. The concept of modularity is created with 207.36 m2 amphibious house system. In a system of amphibious house consists of 4 modular house that each house’s area 51.84 m2. Theme parks have 103.68 m2 area with the length and the width is 7.20 meters and 14.40 meters respectively. Flexibility concept is created by giving freedom to the people to choose the material and space function consist in amphibious homes. Kampung Cieunteung community life will be more flexible because it can live in two conditions. When the flood is occured, residents will use the boat as a major commodity transportation. The concept of diversity is created by the separation into smaller units so that the damage occurs in one modular system does not interfere of overall system. This concept is made by separating building systems and regional land-use planning in the neighborhood as gotong royong in Kampung Cienteung. Urban Climate Resilience approach like safe failure that is used in this design is an attempt to provide solutions for designing flood adaptive community. The approach is more focused on the creation of a residential area that is adaptive to the concept of amphibious house and modular design. Urban Climate Resilience approach to produce the design of residential buildings that are flexible and adapt to the needs and desires for Kampung Cieunteung society.